The nurse’s work environment in a hospital emergency service - José Luís Guedes dos Santos; Fernando Henrique Antunes Menegon; Shara Bianca De Pin; Alacoque Lorenzini Erdmann; Roberta Juliane Tono de Oliveira; Inácio Alberto Pereira Costa (Rev Rene)
Objective: to analyze the characteristics of the nurse’s work environment in a hospital emergency service. Methods: a mixed method study with a concurrent triangulation strategy using data from a descriptiveexploratory study, with 19 nurses, and a Grounded Theory study with three sample groups totaling 21 participants. The quantitative data were collected using the Brazilian Nursing Work Index - Revised and were subjected to descriptive statistical analysis. The qualitative data were obtained from interviews and were analyzed through initial and focused coding. Results: the nurses considered that they had autonomy, good relationships with the physicians, and organizational support. However, the control over the environment was shown to be an unfavorable characteristic. Based on the results, the category: “Seeking to organize the work environment for demand which exceeds attendance capacity” is presented. Conclusion: the characteristics of the emergency environment were shown to be favorable to the nurse’s work, with the exception of control over the environment.